Effect of pyrolysis and temperature on surface chemical properties of palm, bamboo and cypress biochars (UNED Research Journal, 2026)
Introduction: Biochar is a carbonaceous material obtained through the pyrolysis of biomass under oxygen-limited conditions. Its potential for agricultural and environmental applications directly depends on its chemical and structural properties. Pyrolysis temperature and production methods dictate the proportion of oxygenated functional groups, the degree of aromaticity, and mineral content, thus modifying its stability and functionality. Objective: To determine the effect of pyrolysis conditions on the surface chemical properties of biochars derived from oil palm empty fruit bunches, cypress wood, and bamboo. Methods: We used a field-scale kiln (Kon-Tiki) and controlled laboratory conditions (muffle furnace at 400°C, 500°C, 600°C, and 700°C) together with proximal analysis, determination of pH and electrical conductivity, elemental analysis (CHNS/O), zeta potential measurement, Boehm titration, and Fourier-transform infrared spectroscopy (FTIR). Results: Increasing pyrolysis temperature reduced volatile matter while increasing fixed carbon and ash content; pH increased with temperature, whereas field-produced biochars exhibited higher electrical conductivity values. Elemental analysis showed a carbon increase up to 82% and a decrease in oxygen and hydrogen content. Atomic ratios H/Corg and O/Corg decreased progressively, indicating high aromatic stability. Oil palm empty fruit had more nitrogen than bamboo and cypress, with sulfur at trace or undetectable levels. The Zeta potential became less negative at higher temperatures due to surface deoxygenation (confirmed by FTIR and Boehm titration). Biochars retained higher active site density than activated carbon. Conclusions: Laboratory-produced biochars presented more homogeneous properties and structural stability, while field-produced materials exhibited a unique functional duality of a stable core and a reactive periphery. This biochar stands out for its potential nitrogen contribution to the edaphic system.
Keywords: agro-industrial waste; bioeconomy; soil amendment; pyrolysis; aromatic stability; Kon-Tiki kiln